2012
DOI: 10.1093/cid/cis006
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of HIV Drug Resistance in Children Receiving Antiretroviral Therapy: A Pilot Study of the World Health Organization’s Generic Protocol in Maputo, Mozambique

Abstract: Between 2007 and 2008, the Mozambique Ministry of Health conducted an assessment of human immunodeficiency virus drug resistance (HIVDR) using World Health Organization (WHO) methods in a cohort of children initiating antiretroviral therapy (ART) at the main pediatric ART referral center in Mozambique. It was shown that prior to ART initiation 5.4% of children had HIVDR that was associated with nevirapine perinatal exposure (P < .001). Twelve months after ART initiation, 77% had viral load suppression (<1000 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
4
12
0
Order By: Relevance
“…In the multivariable logistic model the mothers that took antiretrovirals to prophylaxis their fetus/infant significantly increased risk of NVP resistance (OR = 48.65) among children comparing to mothers who received ART. This finding corroborates the results observed in Maputo by Vaz et al [ 26 ], substantiating the evidence that sd-NVP-based prophylactic regimens lead to a marked increase in the risk of resistance to this ARV and to the subsequent use of NNRTIs [ 3 , 12 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the multivariable logistic model the mothers that took antiretrovirals to prophylaxis their fetus/infant significantly increased risk of NVP resistance (OR = 48.65) among children comparing to mothers who received ART. This finding corroborates the results observed in Maputo by Vaz et al [ 26 ], substantiating the evidence that sd-NVP-based prophylactic regimens lead to a marked increase in the risk of resistance to this ARV and to the subsequent use of NNRTIs [ 3 , 12 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…Despite gradually improving access to ART, the proportion of children currently treated in the country is considerably small. As of December 2010 only 23% of HIV-infected children aged < 15 years old in need of ART were receiving this therapy [ 26 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though some studies have shown that age is a risk factor for treatment failure [ 36 39 ] and drug resistance [ 40 , 41 ], most likely due to developing metabolic pathways, variable pharmacokinetics and lack of adequate paediatric dosing information, the CHER study did not support this association [ 42 ]. While children who developed major PI mutations in our study were younger at the time of ART initiation than those who did not develop mutations, this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…[73] , [78] , [146] , [148] , [153] , [171] – [173] Co-infections prevalent in the tropics and food shortages are recurring challenges that are far less prevalent in higher income nations. [174] [177] Drug resistance has not been studied widely in Mozambique [178] .…”
Section: Discussionmentioning
confidence: 99%